2018
DOI: 10.1097/mnm.0000000000000839
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of 18F-FDG PET/MRI in recurrent pelvis malignancies of female patients

Abstract: The aim of this study was to assess the diagnostic performance of fluorine-18-fluorodeoxyglucose (F-FDG) PET/MRI for suspected recurrence of pelvis malignancies of female patients using a meta-analysis. We performed a systematical literature search for relevant studies in PubMed, Cochrane Library, Google Scholar, and several Chinese databases. Quality Assessment of Diagnostic Accuracy Studies (QUADAS-2) was used to assess the quality of all included studies. Pooled sensitivity, specificity, positive likelihood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…In a meta-analysis of diagnostic accuracy for detecting recurrent disease with CA-125, 18 F-FDG PET/CT, CT, and MRI, 18 F-FDG PET/CT offered the highest sensitivity of 91%, compared with 69% for CA-125, 79% for CT, and 75% for MRI, suggesting that 18 F-FDG PET/CT could be a useful tool for detecting recurrence, particularly in patients with increased CA-125 and negative CT or MRI (9). In terms of 18 F-FDG PET/MRI, a meta-analysis showed that 18 F-FDG PET/MRI provides excellent diagnostic performance with 96% sensitivity and 95% speci city for restaging female patients with suspected recurrence of gynecological pelvic malignancies (12). Although no signi cant differences were identi ed in comparisons with ceCT in the present study, likely because of the small sample size, 18 F-FDG PET/MRI could detect recurrent lesions in all patients, suggesting that 18 F-FDG PET/MRI might also prove useful for detecting recurrent ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a meta-analysis of diagnostic accuracy for detecting recurrent disease with CA-125, 18 F-FDG PET/CT, CT, and MRI, 18 F-FDG PET/CT offered the highest sensitivity of 91%, compared with 69% for CA-125, 79% for CT, and 75% for MRI, suggesting that 18 F-FDG PET/CT could be a useful tool for detecting recurrence, particularly in patients with increased CA-125 and negative CT or MRI (9). In terms of 18 F-FDG PET/MRI, a meta-analysis showed that 18 F-FDG PET/MRI provides excellent diagnostic performance with 96% sensitivity and 95% speci city for restaging female patients with suspected recurrence of gynecological pelvic malignancies (12). Although no signi cant differences were identi ed in comparisons with ceCT in the present study, likely because of the small sample size, 18 F-FDG PET/MRI could detect recurrent lesions in all patients, suggesting that 18 F-FDG PET/MRI might also prove useful for detecting recurrent ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Swollen lymph nodes larger than 1 cm in short-axis diameter were graded as malignant. For 18 F-FDG PET/MRI interpretations, the classi cation of lymph nodes as cancer-positive was based on the presence of focally appreciable metabolic activity above that of normal muscle; or asymmetric metabolic activity greater than that of normal-appearing lymph nodes at the same level in the contralateral pelvis, in a location corresponding to the lymph node chains on CT or MRI images, with reference to previous reports (12,13). Furthermore, the presence of a central unenhanced area suggesting central necrosis or peripheral low attenuation suggesting a fatty hilum within lymph nodes was considered a benign sign.…”
Section: Image Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta-analysis of diagnostic accuracy for detecting recurrent disease with CA-125, 18 F-FDG PET/CT, CT, and MRI, 18 F-FDG PET/CT offered the highest sensitivity of 91%, compared with 69% for CA-125, 79% for CT, and 75% for MRI, suggesting that 18 F-FDG PET/CT could be a useful tool for detecting recurrence, particularly in patients with increased CA-125 and negative CT or MRI (9). In terms of 18 F-FDG PET/MRI, a meta-analysis showed that 18 F-FDG PET/MRI provides excellent diagnostic performance with 96% sensitivity and 95% speci city for restaging female patients with suspected recurrence of gynecological pelvic malignancies (12). Although no signi cant differences were identi ed in comparisons with ceCT in the present study, likely because of the small sample size, 18 F-FDG PET/MRI could detect recurrent lesions in all patients, suggesting that 18 F-FDG PET/MRI might also prove useful for detecting recurrent ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The new PET modality of 18 F-FDG PET/MRI provides high soft-tissue contrast along with functional imaging of FDG uptake, and has shown potentially better diagnostic performance than 18 F-FDG PET/CT in gynecologic cancers (12,13). In evaluating and characterizing ovarian tumors, fusion of PET and MRI provides advantageous sensitivity and speci city compared with MRI or 18 F-FDG PET/CT (14).…”
Section: Introductionmentioning
confidence: 99%